Identification and Classification of Polymyalgia Rheumatica (PMR) and PMR-Like Syndromes Following Immune Checkpoint Inhibitors (ICIs) Therapy: Discussion Points and Grey Areas Emerging from a Systematic Review of Published Literature - Manzo, Ciro (Medicines (Basel), 2020)
Background: Polymyalgia Rheumatica (PMR) is one of the most frequent rheumatologic immune-related adverse effects (IRAEs) in cancer patients following therapy with immune checkpoint inhibitors (ICIs). Atypical findings in many patients often lead to diagnosing PMR-like syndromes. Materials and methods: The aim of our research was to review reported diagnoses of PMR and PMR-like syndromes following ICIs therapy, and assess whether they can be redefined as adverse drug reaction (ADR). In line with PRISMA guidelines, we carried out a systematic search on three main bibliographic databases, based on a combination of subject headings and free text. We included all studies and case-reports published after 2011 (when FDA approved the use of the first ICI) describing the association of PMR or PMR-like syndromes with all types of ICIs therapy. We excluded reviews, conference abstracts, comments, secondary articles, and non-English language studies. Results: We reviewed data from seven studies and eight case-reports, involving a total of 54 patients. Limitations included: the small size of all studies; only one retrospective study used validated criteria for PMR; most reports assessed IRAEs by clinical judgment only and did not seek validation through assessment scales. To date, it remains a conundrum whether IRAEs-PMR is identical to the idiopathic form of the disease, or whether it should be considered a subset of the disease or a new entity. Conclusions: Our review indicates that the relationship between PMR and ICIs therapy is yet to be clearly understood and defined and that future research should remedy the current limits in study design.